Pagsibol : a biography of Onofre R. Pagsanghan in speeches, songs, and other writings - Totanes, Vernon R. (Quezon City : Bughaw, 2023)
This biography attempts to tell the life story of Onofre R. Pagsanghan using his own words from the 1940s to the 2010s, and organizes them in away that suggests what he would have written if he had ever tried to write an autobiography (which he did not). This book is borne out of a dream that many more will (3z(Bhear(3y (BMr. Pagsi as his students and countless others have heard him. It is hoped that like John the Baptist before him, his words will inspire others to follow, not him, but Jesus.s
Family
Von Totanes
Keywords: Pagsanghan, Onofre, -- 1927-; High school teachers -- Philippines -- Biography; Screenwriters -- Philippines -- Biography